Pengaruh Harga, Lokasi, Kualitas, Promosi, Teknologi serta Layout terhadap Pertumbuhan Usaha Toko Fajar Furniture Kayu Jati Cikarang - Joko Mulyono; Halipi Hazizan (Departement of Mathematics Education, 2023)
This study aims to determine the partial and simultaneous influence between Price, Location, Quality, Promotion, Technology and Layout on the Business Growth of Fajar Funiture Kayu Jati Cikarang Bekasi Store. The research method used in this study is using quantitative research methods. The sampling used in this study is using the Probability Sampling method and the type of sampling uses simple random sampling. The results showed that prices and promotions had a significant and partial positive effect on the business growth of Toko Fajar Funiture Kayu Jati Cikarang Bekasi. Location, product quality, technology and layout do not have a partial effect on the business growth of Toko Fajar Funiture Kayu Jati Cikarang Bekasi. Independent variables have a positive and significant effect simultaneously on the business growth of Toko Fajar Funiture Kayu Jati Cikarang Bekasi.